Comparison Study Between the Experimental and Finite Element Analysis (FEA) on a Static Load of Magnesium AZ31B as Biodegradable Bone Plate Material - Wicaksono, Mahruri Arif; Sukmana, Irza; Akhmad Riszal; Hendronursito, Yusup; Nazarrudin, Rizal; Haviz, Muhammad (Jurnal Inovasi Teknologi, 2024)
Biomaterials is an advanced material engineering technology that is used to help heal bone fractures or fractures. Currently, many biomaterials use materials such as titanium alloy, stainless steel, platinum, and chromium, but these materials cannot be degraded naturally so a second operation must be carried out to remove the installed biomaterial. Biomaterials are temporary in nature so when the bone returns to its original state, the biomaterial must be surgically removed. Research was conducted to obtain a design with a material that can be naturally degraded without causing toxicity. Magnesium AZ31B is a recommended candidate as a base material for degradable bone implants. Magnesium AZ31B material, it is expected to reduce or minimize the surgical removal of implant biomaterials. Bone plate geometry  use plate  bone  dimension 150mm x 15mm x 3mm with  variation 10 hole parallel and zigzag as well as with a bolt  bone  dimensions  long 40 mm with pitch 1mm diameter 5mm. Test bending was conducted  with ASTM E290-14 showing  that on plate  bone  hole parallel  with  burden  maximum 33,419 KN with a deformation  maximum of 30.89 mm whereas  for  plate  bone  hole zig zag with the burden  maximum 32,863 KN with  deformation  maximum big as 29.97 mm. From the study  experimental  that  plate  bone  hole  parallel  have  nature  mechanic  more  tall  compared  with  plate  bone  hole zig Zag although  with the difference which is not significant. Whereas on simulation FEA plate bone  hole  parallel  with  burden 33,419 KN get  results total deformation  as big as 31,481 mm with von Mises stress 15,337 MPa, then  for  plate  bone  hole zig Zag with  burden 32,863 KN with total deformation 32.466 mm and von Mises stress as big as 33,948 MPa. In testing by  experiment and simulation FEA plate  bone  hole  parallel  get  difference  around 0.591 mm or 0.94% whereas  for  plate  bone  hole zig Zag in  testing  by  experiment and simulation  get  difference  around 2,893 mm or 4.60%.